The Role of Diniyah Madrasah Teachers in Fostering Discipline in Student Learning at Islamic Boarding Schools - Lisa Nur Aini; Eni Fariyatul Fahyuni (Adabiyah: Jurnal Pendidikan Islam, 2022)
Students' learning discipline is the obedience of students to carry out their learning obligations, so they can get changes in themselves, both studying at home and in Islamic boarding schools. Madrasah diniyah teachers have a very big responsibility in disciplining their students to obey the rules that exist in Islamic boarding schools. Therefore, this study aims to determine the role of madrasah diniyah teachers in fostering student learning discipline as well as supporting and inhibiting factors in fostering student learning discipline. This research is a descriptive qualitative research, namely research that describes the reality and circumstances of the object of research in accordance with the facts in the field by taking data that is what it is. In this study, the informants were madrasah diniyah administrators, madrasah diniyah teachers, and students of Islamic boarding schools. The location of this research was conducted in Paciran Village, Paciran District, Lamongan Regency. Data collection techniques are interviews, observation, documentation. The data collection technique uses Miles and Huberman which consists of four components of analysis, namely data reduction, data presentation, conclusion drawing, data int erpretation. Based on the research that has been done, there are research results, namely: 1). The role of madrasah diniyah teachers in fostering learning discipline for students at the Muhammadiyah Karangasem Islamic boarding school. 2). How the supporting and inhibiting factors for madrasah diniyah teachers in fostering student learning discipline include the teacher in teaching, the suitability of the subject matter to be delivered, and sufficient learning time.